Developing a Research Design based on the distinction of History from the Social Sciences - Rafia Riaz; Amanullah Khan (Journal of Research in Social Sciences, 2024)
The issues of methodology are mainly associated with the concept of authenticity and verification of knowledge which is a key element of epistemology. Since antiquity, various solutions have been proposed and methods were evolved in order to ensure accuracy and truthfulness of the knowledge gained. As far as history was concerned, its methods were evolved in its own epistemological framework in ancient and medieval times. However after the development of philosophy of science in the west, the discipline of history had to face severe methodological crisis. Some major philosophers of history after an evolutionary process rejected the methods of sciences; however the discipline is still somehow related with the social sciences. The present research argues that history is even different, ancient and unique from the social sciences. Thus the methods of research in history are entirely different and building a research design in history is a completely different task. The present research has evaluated the evolution of development of methods in the social sciences as well as in history in order to draw a distinction of social sciences from history. The study further proposed a historical research design which is based on the traditional methods of research in history; and which also ensures maximum authenticity by using tools of reliability. The study will help the historians to highlight the actual methodological nature of their discipline and to justify the claims of their researches as authentic and different from the rest of the social sciences at the same time.